https://doi.org/ 10 The Microbiological Relationship Between Drinking Water and Stunting Incidence in the Tanjung Harapan Community Health Center Work Area, North Bengkulu, in 2024 - Widada, Agus; Yusmidiarti, Yusmidiarti; Mualim, Mualim; Utomo, Budi; Lagiono, Lagiono (BIOEDUSCIENCE, 2025)
Background: Stunting is a condition of growth failure in children (body and brain growth) due to prolonged malnutrition. Based on data from the Argamakmur Health Office, North Bengkulu, 212 out of ten villages have cases of stunting in toddlers. Various factors, including the bacteriological quality of drinking water, can cause stunting. Bacteriological quality that does not meet standards increases the risk of diarrhea in toddlers. The purpose of this study was to determine the relationship between the bacteriological quality of drinking water and the incidence of stunting. Methods: The research method used in this study was an observational, descriptive approach.case controlby taking primary data from laboratory test results to see Total Coliform andE. Coliin drinking water. The sample of this study was clean water used by families in the stunting and non-stunting groups at the Tanjung Harapan Community Health Center, North Bengkulu, comprising 60 drinking water samples: 30 from stunting families and 30 from the non-stunting group. Sampling was carried out randomly using simple random sampling. Data analysis using statistical tests, chi-square. Results: The study on the microbiological quality of drinking water, with a total coliform indicator of 71.7%, did not meet the requirements; the indicator for the presence of E. coli at 73.3% also did not meet the criteria. Bivariate tests showed a relationship between the bacteriological quality of drinking water (Total Coliform) and the incidence of stunting, with a p-value <0.05 (0.004) and an OR = 7.875 (CI = 95% 1.958 – 31.675). There is a relationship between the bacteriological quality of drinking water (E. coli) and the incidence of stunting, with a p-value <0.05 (0.009) and an OR of 6.882 (CI = 95% 1.707 – 27.752). Conclusion: To improve the microbiological quality of drinking water, it is hoped that the community will consume drinking water from cooking and drinking water sources that meet microbial requirements.